Relationship between Serum Lipid Profile and Hypertension - Gorial, Faiq I.; Abdul Hameed, Jamal R.; Yassen, Najah Sh.; nama, Mahdi k. (Journal of the Faculty of Medicine Baghdad, 2012)
Background:Dyslipideamia is an important major risk factor for cardiovascular disease (CVD), which is the leading cause of death in the developed and developing countries. The world health organization estimates that dyslipideamia is associated with more than half of global cases of ischemic heart disease and more than 4 million deaths per year. Objective:To assess the serum lipid profile in hypertensive patients. Patients and methods: A case – control study was carried out at AL – Mustansyria , AL- Dubbat primary care centers for family Medicine and Medical city out patients clinic.Lipid profile were studied in 100 hypertensive patients and 100 healthy volunteers individuals attending these clinics matched for age and sex, serving as a control group. Full history was taken, complete clinical examination was done and various laboratory investigations were carried for all individuals in both groups. Results: The mean age was (50.9±9.1)year ; (49.7±9.7)year for hypertensive and control individuals. With 50 % for males and females in both groups. The hypertensive patients had significantly higher body mass index than controls (P=0.005).The hypertensive patients had significantly higher total cholesterol (TC), triglycerides (TG), low density lipoprotein (LDL), and lower high density lipoprotein (HDL),( 204.6±20.8, 162.7±45.2,126.0±23.0, 46.1±7.4) , than control group (176.0±11.8, 151.5± 120.8, 102.6±121.6, 56.2±7.5). In hypertensive patients the TC was significantly increasing with age, overweight, and more in males than females. The TG were slightly more in males than females. LDL had increasing value with gender and BMI. Also there is significant association between serum HDL and obesity in both hypertensive and control patients but more with hypertensive patients. Conclusion:There is a significant relationship between dyslipideamia, B.M.I and hypertension.